Examining the influence of human and psychological capital variables on post-secondary students' academic stress. Issue 12 (2nd December 2022) - Lisnyj, Konrad; Pearl, David L.; McWhirter, Jennifer E.; Papadopoulos, Andrew
ABSTRACT : Purpose: We examined the influence of human and psychological capital variables on the reporting of stress affecting Canadian post-secondary students' academic performances. Methods: This cross-sectional study used the Spring 2019 National College Health Assessment-II data collected across 58 Canadian post-secondary institutions from 55, 284 respondents. Of this, 31, 091 undergraduate students indicated being stressed in the past year and were included in this analysis. Ten variables were selected based on their relevance to human and psychological capital in the literature, and an additional seven socio-demographic variables were adjusted for in subsequent analyses. The associations between these explanatory variables and stress impacting students' academic performances were examined by fitting mixed univariable and mixed multivariable logistic regression models. Results: Students who had a high cumulative grade point average, received information on stress reduction, were aware of mental health resources on campus, felt experiences that challenged them to grow and become a better person, felt their life had a sense of direction or meaning to it, felt interested in life, felt confident, and felt they had something important to contribute to society reported significantly lower odds of experiencing stress that negatively impacted their academic performance. Students who previously utilized psychological or mental health services and who felt hopeless reported significantly higher odds of experiencing stress affecting their academic performance. Conclusion: Targeting these components within post-secondary institutions may cultivate human and psychological capital, mitigate the deleterious effects of stress affecting academic success, and promote intrapersonal resiliency skill-building among students.